PERBANDINGAN KEMAMPUAN ANAK USIA 3 TAHUN DALAM PENGUASAAN BAHASA BALI SEBAGAI SARANA KOMUNIKASI (KAJIAN PSIKOLINGUISTIK) - Komang Puteri Yadnya Diari; I Made Sunaryana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Humans interact with one another through communication in the form of language. Communication occurs, both verbally and nonverbally, namely by writing, reading, and signs or symbols. The language acquisition requires a process according to the stages of age. The purpose of this study was to determine the comparison of Balinese language development between two children aged 0-3 years, namely Juna and Bayu in terms of phonological development. This research used observation and interview methods to gather data from Juna and Bayu families in terms of how they arranged words and sentences correctly and the interaction with their families. The children's language development is influenced by environmental factors that apply motherese, recasting, echoing, expanding.Keywords: Comparison of children's language, Psycholinguistics